Mapping Conflict Issues of Sand Mining, Study of Conflict Governance Natural Resource Management - Saiman, Saiman; Salahudin, Salahudin; Loilatu, Mohammad Jafar; Putra, Muhammad Jovan Patriot (Jurnal Studi Pemerintahan, 2025)
This study aims to map the issue of sand mining conflict in the Special Region of Yogyakarta (DIY). Illegal mining in DIY has caused a significant impact on environmental damage, creating a water crisis and changing natural vegetation. Within thirteen years, the issue of illicit mining in DIY has not been resolved due to slow policies and responses. This study uses a qualitative method to map the issue of illegal mining and the impacts caused, and it uses Nvivo as an analysis tool to map the issue of illicit mining in DIY. The results of this study answer that illegal mining in DIY is grouped into conflict issues, causes of conflict, impacts of conflict, and conflict resolution. Mapping the results of this study shows that the water crisis and environmental damage cause the issue of conflict, while the causes of the conflict are sand degrading and illegal mining permits. The loss of water sources and agricultural areas causes the impacts. Conflict resolution through the closure of sand mines and government policies, this study concludes that the consistency of the issue of illegal mining is influenced by the impacts caused and the intensity of mining carried out, so illegal mining in DIY persists for a long time.